ANALISIS PEMILIHAN MODA TRANSPORTASI UNTUK PERJALANAN KERJA - Putu Widiarta, Ida Bagus (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 2 Juli 2010)
Optimisation of public transport use (such as angkot or microbus) is required due to the difficulty to increase the roadway capacity by widening of road in order to manage supply. Therefore, an alternative approach is required by managing transport demand so that the system can be controlled. This approach is required especially for the new developed housing in Dalung Village, Badung Regency. Dalung area (in North Kuta District) is part of Samigita development project where the the number or people travelling to work are about 613 persons (189 persons working in public service and 424 persons in private company). The majority of people in this area are travelling by private vehicles. One aspect that needs to be studied is the general cost for the journey to work both by private vehicles (motor bikes) and public transport. Mode choice model used is Binomial Logit Model. The model equation is Log {(1 – PP ) / PP} = 2,248 – 0,001 (CP – CU). Results of analyses indicate that if the cost difference between public transport and private transport increases, the probability of using private vehicles will increase; Although the cost of the two modes of transportation is set at the same cost, the majority of workers will still use private vehicles (about 79%), and this is also the case even when the cost difference is Rp 2.800,00. The cost balance between private vehicles and public transport is achieved when the cost of using private vehicles is about 1.4 times more than public transport cost.
Keywords: Mode Choice, Journey to Work, Binomial Logit Model